TECHNICAL FEASIBILITY ANALYSIS OF A SOLAR-POWERED AGRICULTURAL PRODUCE DRYER FOR STRENGTHENING THE RURAL ECONOMY IN SIMALUNGUN REGENCY - Immanuelta Sitepu (Program Pascasarjana UIN Sumatera Utara, 2026)
Postharvest handling of agricultural products in Simalungun Regency is still dominated by open sun drying, which is highly dependent on weather conditions, vulnerable to contamination, and often produces uneven levels of dryness. This study aims to analyze the technical feasibility of a solar-powered agricultural product dryer and its contribution to strengthening the rural economy. The study employed a descriptive qualitative approach, using primary data obtained through in-depth interviews and observations, as well as secondary data derived from technical documentation, production records, quality standards, and price information. Data were analyzed through data reduction, data display, conclusion drawing, and source triangulation. The findings indicate that the dryer was capable of increasing temperature, protecting products, accelerating moisture reduction, and improving product quality. However, its technical feasibility depended on equipment design, air circulation, load capacity, operator competence, and the governance of its utilization. The machine was therefore considered feasible for further development, provided that it is supported by adequate training, maintenance, and farmer-group management.